Scoping review of global control strategies for Echinococcus granulosus sensu lato - De la Cruz-Saldaña, Tania A. (2025)
Objectives: Echinococcus granulosus sensu lato (EG) causes cystic echinococcosis (CE), a neglected zoonotic disease with a global control burden in the billions of dollars. We provide a comprehensive overview of EG control interventions worldwide. Methods: We followed the Arksey and O'Malley Framework. We identified and coded selected articles and classified the data based on target host, type of study, and control mechanism. We described each intervention's efficacy, safety, barriers, and facilitators. Critical appraisal was conducted independently by two reviewers using the Mixed Methods Appraisal Tool. Results: We screened 7853 studies and analyzed seven on human interventions, 21 on animals, and 17 on both. Human studies focused mostly on educational strategies and monitoring. Animal studies focused predominantly on praziquantel (PZQ) for dogs and the EG95 vaccine for sheep. Animal and human studies were larger, longer, and covered wider areas. Overall, study quality was moderate to low. Conclusions: Long-term interventions targeting animals and humans can significantly reduce EG transmission, particularly when PZQ is included. Higher-quality evidence, standardized methods, and better reporting on post-intervention outcomes are necessary to draw stronger conclusions and assess the sustainability and scalability of control measures. A One Health approach is essential for integrating and sustaining long-term EG control efforts.